Evaluating Advanced Plate Fixation Techniques for Distal Femoral Fractures in Elderly Patients - Ahmad Saad (AlQalam Journal of Medical and Applied Sciences, 2025)
Distal femoral fractures are a growing concern among geriatric patients due to osteoporosis and age-related fragility. This study evaluates the effectiveness of LOCKED COMPRESSION PLATES (LCPs) in the surgical management of these fractures. Fifty elderly patients with fractures classified by the AO system underwent LCP fixation at Al-Beida Medical Center. Outcomes included radiological union, functional recovery assessed by the Knee Society Score (KSS), and complication rates. Radiological union was achieved in all cases within an average of 12.7 weeks. Functional recovery was excellent for Type A fractures (KSS 93), satisfactory for Type B (KSS 88), and moderate for Type C (KSS 80). Complication rates were low (10%), with no cases of nonunion or deep infection. LCPs offer biomechanical stability and promote early mobilization, making them effective for managing osteoporotic distal femoral fractures. Further studies are needed to compare their performance with other fixation techniques. تعد كسور الفخذ السفلي من القضايا المتزايدة بين المرضى كبار السن بسبب هشاشة العظام وضعف العظام المرتبط بالعمر. تقيّم هذه الدراسة فعالية الألواح المثبتة بالضغط المغلق في العلاج الجراحي لهذه الكسور. خضع خمسون مريضاً مسناً مصاباً بكسور مصنفة وفقاً لنظام جمعية دراسة التثبيت الداخلي للتثبيت بالالواح المثبتة بالضغط المغلق في مركز البيضاء الطبي. شملت النتائج إلتحام الكسور شعاعيا، والتعافي الوظيفي المقيم باستخدام مقياس جمعية الركبة و معدلات المضاعفات. تم تحقيق التحام شعاعي في جميع الحالات في غضون متوسط قدره 12.7 أسبوعًا. كان التعافي الوظيفي ممتازًا للكسور من النوع A , ، ومرضياً للنوعB، ومتوسطًا للنوع . C كانت معدلات المضاعفات منخفضة (10%)، مع عدم وجود حالات فشل التئام أو إصابة عميقة. توفر الألواح المثبتة بالضغط المغلق استقرارًا بيوميكانيكيًا وتعزز التحرك المبكر، مما يجعلها فعالة في إدارة كسور الفخذ السفلي الناتجة عن هشاشة العظام. هناك حاجة إلى دراسات إضافية لمقارنة أدائها مع تقنيات التثبيت الأخرى